Drivers of beer pricing in Argentina - Larrosa, Juan Manuel Ceferino (2024)
This study uses web data from the retail beer segment to explore beer pricing dynamics in Argentina amid chronic inflation. We address three main questions: the impact of product attributes on pricing under high inflation, evolving pricing patterns over time, and the effect of the 2020 lockdown. Our analysis unveils the interplay between product attributes, seasonal trends, and inflationary pressures in shaping pricing strategies. While inflation drives rapid adjustments, seasonal trends and product attributes significantly influence pricing decisions. Consumers can benefit from insights into currency fluctuations, fuel costs, and seasonal variations. Beer industry managers can refine pricing strategies to maximize revenue potential amidst economic volatility.